2004
DOI: 10.1021/la048818b
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of Aromatic Carboxylate Anions To Be Planar To Induce Growth of Cationic Micelles

Abstract: It is well-known that some aromatic anions have the ability to induce viscoelastic transformation in aqueous solutions of cationic surfactants even at added salt concentrations as low as 10-20 mM. This behavior is associated with the formation of an entangled network of elongated micelles. However, the effect of aromatic ring substituents on the anion's ability to promote rapid micelle growth is not well-understood. We have performed ab initio calculations of the carbonyl group rotation barriers in a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…This has built on previous work showing that hydrotropes can cause micellar growth in both aqueous systems 32,34 and in w/o microemulsions with AOT 33 . For water-in-oil microemulsions, w value and hydrotrope mole fraction were shown to affect the degree of elongation and enhanced anisotropy of the microemulsion nano-domains.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This has built on previous work showing that hydrotropes can cause micellar growth in both aqueous systems 32,34 and in w/o microemulsions with AOT 33 . For water-in-oil microemulsions, w value and hydrotrope mole fraction were shown to affect the degree of elongation and enhanced anisotropy of the microemulsion nano-domains.…”
Section: Discussionmentioning
confidence: 93%
“…Another approach to form rod-like micelles in alkane solvents is using surfactant/hydrotrope mixtures [32][33][34][35] . Hydrotropes are small amphiphilic molecules which have hydrophilic character, and the ability to increase solubility of organic compounds in water [36][37][38] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a bulky hydrotrope is recognised as being critical for micellar elongation, with these systems shown to produce substantial increases in solution viscosities [10]. Close investigation by NMR and computer simulations revealed that the hydrotrope counterions adsorb at the micellar interfacial region [11]. In mixed solutions of surfactants and hydrotropes of the same charge only ellipsoidal structures have been observed [12].…”
Section: Introductionmentioning
confidence: 99%
“…AOT). 11 And even for those specifically designed surfactants that effectively stabilise 13 water-in-CO2 (w/c) microemulsions, modification of the self-assembled structures, which 14 has been well-established as an effective method to enhance the viscosity in alkane solvent, 15 is generally inhibited in scCO2. 16 In one of the very few reports on anisotropic self-assembled structures in scCO2, it was 17 found that by exchanging the surfactant counter ion Na + with divalent species such as Co 2+ 18 and Ni 2+ , a sphere-rod shape transition can be obtained for the micelles formed not only in 19 alkane solvents with hydrocarbon surfactants, 12 but also in scCO2.…”
mentioning
confidence: 99%